Class Struggle, Dictatorship and Democracy : How the Common People Defeated Francoism (1939-1979) - Domènech, Xavier (Marx and Marxisms: new horizons., 2025)
In Class Struggle, Dictatorship and Democracy: How the Common People Defeated Francoism (1939-1979), historian Xavier Domènech Sampere tells the story of Franco's dictatorship, the struggle for freedoms and the foundations on which democracy was shaped. From the perspective of history from below and based on the analysis of the class struggle, Domènech offers not only a fascinating insight into the experiences of the workers who suffered one of the harshest and longest dictatorships in European history but also of the businessmen who benefited from it. The relationship between social movements and political change and the perspective of class conflict gives this book a unique perspective for understanding both the dictatorship and the arrival of democracy and its foundations. Published for the first time in English, Class Struggle, Dictatorship and Democracy: How the Common People Defeated Francoism (1939-1979) is a must read for all those interested in the history of fascism, social movements, and political transitions.